Psychologische Probleme und Erkenntnisse zur Textauswahl für den fremdsprachigen Lehr- und Lernprozeß - Apelt, Walter (Wydawcnictwo Naukowe UAM, 1986)
The interest linguistics shows in the text manifests itself in a global orientation (synthetic, contextual) and consists in linguistic-total approach: from the general to the particular and back to the general. It also finds its reflection in the methodology of FLT. The author criticizes the recently prevailing communicative approach; then ha gives the results of research on the contents of texts (as far as their motivational and anti-motivational aspects are concerned).